Unpacking the mysteries of Parvovirus B19 Myocarditis - Hassan, Karim; Doubell, Anton; Herbst, Philip (SA Heart Journal, 2022)
Myocarditis is an inflammatory disease of the heart muscle, most often caused by viral infections. Its diagnosis can be difficult due to the heterogeneity of presentations that often mimic other common cardiological conditions, such as acute coronary syndrome (ACS) and heart failure. Although most cases are benign and self-limiting, it can also take on a more malignant course complicated by life-threatening arrhythmias, cardiogenic shock, and sudden cardiac death (SCD). A certain proportion of patients progress to develop dilated cardiomyopathies (DCMO). The developed world has experienced a shift in viral pathogens detected in patients with acute myocarditis over the past 20 years, and Parvovirus B19 (PVB19) and human herpesvirus-6 (HHV6) are currently the most commonly identified viruses in the myocardium of patients with viral myocarditis. The clinical relevance and pathological roles of these viruses however remain questioned. This focused review aims to use 2 cases of PVB19 myocarditis managed by our unit to explore issues related to the clinical presentation, diagnosis, treatment and prognosis of PVB19 myocarditis along with controversies surrounding the pathogenic role and clinical relevance of PVB19 in myocarditis. SAHeart 2022;19:28-37